Fusion cuisine in the shadow of Mount Olympus: an integrated study of Middle and Late Bronze Age cooking pots - Dimoula, Anastasia; Koulidou, Sophia; Tsirtsoni, Zoi; Standall, Edward; Craig, Oliver E.; Valamoti, Soultana Maria (Journal of Greek Archaeology, 2022)
This paper explores the relations developed between Mycenaeans and their northern neighbours through the study of cooking assemblages from four sites in the region of Pieria, in present-day Greek Central Macedonia. A strong connection with the Mycenaean sphere in the 13th -12th century BC has already been indicated through archaeological evidence from graves, but it is the first time that this connection is explored through domestic utensils. Moreover, the four sites cover chronologically the entire Middle and Late Bronze Age – i.e., a time interval corresponding to the whole of the Mycenaean period and the centuries immediately preceding it, c.2000–1100 BC – providing both wide contexts and great time depth. Through a ‘longue durée’ investigation of food preparation using ceramic analysis and contextual associations, we evaluate local and traditional elements of the cooking apparatus vs. new and/or exogenous ones, and identify the time of their introduction. Based on our observations we discuss cultural interaction between the Mycenaean and northern Greek communities as expressed through food preparation, in other words, the transformation of cooking within the specific social and historical contexts of our case studies.